Spirit of the snowpeople - Keyes, Diane (Down East Books, 2008)
During a particularly long winter, residents of a small northwoods community build a village of snowpeople that brings joy to visitors from far and near, and when the sculptures begin to melt an elder explains that their spirit will live on throughout the seasons.